Lift the Flap Questions & Answers about your Body (Usborne Lift-the-Flap-Books) - Katie Daynes (London Usborne Publishing Ltd., 2013)
Children are always asking questions and their bodies are an endless source of fascination to them. This quirkily illustrated book has lots of answers and will engross curious children. You can find the answers to intriguing questions such as How do I smell things? What makes me burp? Why do I need to wash my hands? Why is blood red? And lots more. It offers friendly, simple answers to challenging questions, with entertaining and informative illustrations.